THE IMPACT OF EXTERNAL AUDIT RISKS ON INTERNAL CONTROL AND AUDIT SYSTEMS: AN EMPIRICAL STUDY AT THE IRAQI NATIONAL BANK OF THE MIDDLE EAST - Mohammad Abdulwahid Jayyas (PT. Antis International Publisher, 2026)
Objective : This study seeks to examine how risks from external oversight affect the success of internal control and auditing processes, using a real-world example from the Middle East National Bank in Iraq. The significance of this subject arises from the delicate and complicated relationship between external oversight – shown by organisations like the Central Bank and the Financial Supervision Bureau – and internal control, shown by the bank’s audit departments. If there is insufficient cooperation or if there is confusion between these two groups, it can result in a decrease in the effectiveness of the overall monitoring system. Method : The study used a descriptive analytical approach, and information was gathered through a survey given to a chosen group of employees in departments that handle internal control and auditing. Additionally, this was enhanced by informal interviews with several internal audit and financial control staff, which enabled a combined quantitative and qualitative review. The quantitative portion included 85 participants, and the information was examined using SPSS, applying descriptive statistics, linear regression analysis, and a reliability check using Cronbach's alpha coefficient. Results : The findings indicate that while external oversight is important, it can also introduce risks related to management and structure that can hinder the independence and effectiveness of internal auditing. The study further revealed that 63% of the variations in how effective internal audits are can be attributed to the risks posed by external control (R² coefficient = 0. 63). Additionally, there is a redundancy in control processes and confusion regarding the assignment of responsibilities. Descriptive statistics showed that the area concerning